Productizing Quantum Computing Bring Quantum Computing Into Your Organization - Agarwal, Dhairyya; D, Shalini; Ganguly, Srinjoy (Berkeley, CA : Apress : Imprint: Apress, 2023)
Leverage the benefits of quantum computing by identifying business use cases and understanding how to design and develop quantum products and services. This book will guide you to effectively productize quantum computing, including best practices, recommendations, and proven methods to help you navigate the challenges and risks of this emerging technology. The book starts with a thorough introduction to quantum computing, followed by its various algorithms and applications. You will then learn how to build a strong foundation in classical computing, seek practical experience, and stay up-to-date with the latest developments in the field. Moving forward, you will gain an understanding of how to conduct market research to identify business opportunities for quantum computing products and services. The authors then guide you through the process of developing a quantum roadmap and integrating quantum computing into an existing system. This is concluded by a demonstration of how to managequantum computing projects and how to address their risks and challenges. After reading this book, you will understand quantum computing and how it can be applied to real-world business problems. You will: Identify business use cases for quantum computing and understand the potential benefits and risks of quantum applications Design and develop quantum products and services by identifying quantum algorithms, programming in quantum languages, and leveraging quantum simulators and hardware Integrate quantum computing into existing systems Integrate quantum algorithms with classical algorithms.
Chapter 1: Introduction to Quantum Computing -- Chapter 2: Quantum Algorithms and Applications -- Chapter 3: Continue Learning About Quantum Computing -- Chapter 4: Assessing the Market and Competitive Landscape -- Chapter 5: Designing Quantum Products and Services -- Chapter 6: Developing a Quantum Roadmap -- Chapter 7:Integrating Quantum Computing into an Existing System -- Chapter 8:Releasing Quantum Computing-based Products -- Chapter 9: Challenges and Risk in Productizing Quantum Computing.
Keywords: Software engineering -- Management; Software Management